Radar Cross-section of a target and attenuation of electromagnetic waves in sandstorms. (January 2023) - Ma, Jiaoyan; Jin, Ke; Zheng, Xiaojing
Highlights: A model for predicting the electromagnetic wave attenuation and calculating the RCS of isotropic target with arbitrary shape in sandstorms was proposed. The effect of the non-uniform charged sand particles on the target's RCS was discussed with the model. An empirical formula is presented to calculate the RCS of an arbitrary shape metal target in homogeneous lossy medium. Abstract: The sand particles suspended in the atmosphere can cause the attenuation of electromagnetic waves (EWs) and affect the electromagnetic scattering properties of a target during sandstorms. In this study, a theoretical analysis is offered for the prediction of the EWs attenuation and the radar cross section (RCS) of a target in sandstorms. In the model, an equivalent medium approximation is performed by considering the non-uniform charge distribution on the sand particles, and the effect of the charged sand particles on the scattering characteristics of a target is also taken into account. Numerical results show that the RCS of a target is severely affected in sandstorms. Besides, the charged sand particles have a much greater effect on the target's RCS than the case of the uncharged sand particles. It can be found that the average variation value of the target's RCS decreases nearly exponentially with the increase of visibility, and increases nearly linearly with the distance between the target and incident wave source. Finally, an empirical formula is presented to calculate the RCS of an arbitrarily shaped metal target in a homogeneous lossy medium. These investigations will be of significant benefit to radar detection technology in sandstorms.